2018
DOI: 10.1016/j.tsf.2018.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of high-entropy alloy thin films as candidates for coating nuclear fuel cladding alloys

Abstract: HighlightsIon beam sputter-deposition was used to produce thin films from the system FeCrMnNi.Two thin films were obtained at same deposition conditions. The high-entropy alloy thin film exhibited grains with sizes around 100 -200 nm.The non-equiatomic thin film exhibited grains with sizes around of 40 nm.High-entropy alloy and nucleation theories are used to reflect on the results. AbstractThin films of the quaternary system FeCrMnNi were synthesised by ion beam sputterdeposition. The films were deposited on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In order to reduce or possibly suppress the RIS effect, MAX Phases [43] and High-Entropy Alloys [44,45] should be taken into consideration for future radiation damage and tribology studies on coating Zr-based alloys for the nuclear industry. The intense recent research on these materials have indicated a potential high phase stability under energetic particle bombardment when compared with conventional ceramic materials and metallic alloys, and this could imply -from a microstructural perspective -a superior tolerance against the multiple deleterious effects of energetic particle irradiation [43,45].…”
Section: Resultsmentioning
confidence: 99%
“…In order to reduce or possibly suppress the RIS effect, MAX Phases [43] and High-Entropy Alloys [44,45] should be taken into consideration for future radiation damage and tribology studies on coating Zr-based alloys for the nuclear industry. The intense recent research on these materials have indicated a potential high phase stability under energetic particle bombardment when compared with conventional ceramic materials and metallic alloys, and this could imply -from a microstructural perspective -a superior tolerance against the multiple deleterious effects of energetic particle irradiation [43,45].…”
Section: Resultsmentioning
confidence: 99%
“…A useful lookup tool for the neutron scattering and capture cross sections for elements as a function of neutron energy is the TENDL nuclear data library [ 27 ]. A number of studies have used low neutron cross section elements to design HEAs for ATF cladding, either as bulk alloys [ 28 , 29 , 30 , 31 ] or as coatings for Zr alloys [ 32 , 33 , 34 , 35 , 36 ]. Preliminary results of the HEA coatings has suggested better wear and corrosion performance than uncoated Zr, and authors have claimed they are good candidates for ATF cladding [ 33 , 34 ].…”
Section: Desired Properties and Element Restrictionsmentioning
confidence: 99%
“…Compared with other ATF candidate claddings, the coated Zr alloy is the easiest and most economic approach, which is supposed to the near-term choice for ATF cladding application. Some coating materials have been investigated, including pure metals [17][18][19][20] , alloys [21][22][23] , ceramics 24,25 , and MAX phases 8,26 , among which, the metallic Cr coatings exhibit good resistance to oxidation in both normal condition and accident condition (e.g., LOCA) 6,[17][18][19][20] . This has boosted extensive studies on the Cr-coated Zr alloy cladding during the last decade.…”
Section: Introductionmentioning
confidence: 99%